Alexander von Humboldts Klimatologie in der Zirkulation von Wissen: Historisch-kritische Edition der Berliner Briefe (1830-1859) und ihre Kontexte - Schicht, Katja (Georg Olms Verlag, 2023)
In this dissertation, all surviving letters, letter fragments and supplementary documents that Alexander von Humboldt exchanged with the Berliners Heinrich Wilhelm Dove, Carl Ferdinand Schneider and Jakob Philipp Wolfers on the subjects of meteorology and climatology in the period from 1830 to 1859 are edited in a historical-critical manner. Their replies are also edited, insofar as they have survived. This edition of the letters is intended to close another gap in the series of Humboldt editions that is significant in the history of science. These documents are revealing for several reasons. Firstly, because they document the beginnings of modern climatology. But they are also informative because Humboldt's interdisciplinary research and his work with various institutions can be seen in exemplary fashion. Finally, the material processed here is part of the decisive preparatory work for the "Cosmos" and the "Smaller Writings", insofar as it deals with the thematic area of weather and climate. A detailed overview commentary places all text carriers in broad historical contexts.